Crisis Management Practices and Secondary School Stability in Insecurity-Prone Areas of Zamfara State, Nigeria - Sule Muhammad; Abbas Sani Dahiru (Elementaria: Journal of Educational Research, 2025)
This study examined crisis management practices and their relationship with secondary school stability in insecurity-prone areas of Zamfara State, Nigeria. Persistent insecurity arising from banditry, kidnapping, and communal violence has continued to disrupt school operations, making effective crisis management essential for sustaining educational activities. The study adopted a descriptive survey research design. The population comprised 3,812 principals and teachers in public secondary schools within insecurity-affected areas of Zamfara State, from which a sample of 346 respondents was selected using the Research Advisors (2006) sample size determination table. Data were collected using a structured questionnaire based on a 4-point Likert scale. Descriptive statistics (mean and standard deviation) were used to answer the research questions, while Pearson Product Moment Correlation (PPMC) was employed to test the hypothesis at the 0.05 level of significance. Findings revealed that crisis management practices were implemented to a high extent overall, with safety drills and collaboration with community leaders being more prominent than formal planning, staff training, and communication systems. The study also found that challenges such as inadequate infrastructure, insufficient safety equipment, high community insecurity, and limited funding significantly hinder effective crisis management. Furthermore, a moderate positive and statistically significant relationship was established between crisis management practices and school stability (r = 0.564, p < 0.05). The study concludes that strengthening crisis management frameworks can enhance school stability in insecurity-prone contexts. It therefore recommends improved funding, comprehensive crisis planning, regular staff training, and stronger collaboration with security agencies and community stakeholders.